2013
DOI: 10.1016/j.jcmg.2012.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Low to Moderate Dose Anthracycline-Based Chemotherapy Is Associated With Early Noninvasive Imaging Evidence of Subclinical Cardiovascular Disease

Abstract: Objective To determine if low to moderate doses of anthracycline-based chemotherapy (Anth-bC) are associated with subclinical cardiovascular (CV) injury. Background Cancer survivors that receive Anth-bC experience premature CV events. It is unknown whether low to moderate doses of anthracyclines a) promote early subclinical CV disease manifested by deteriorations in left ventricular ejection fraction (LVEF) or increases in aortic stiffness, or b) are associated with change in quality of life (QOL). Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
254
4
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(285 citation statements)
references
References 32 publications
14
254
4
13
Order By: Relevance
“…In the study revealed a rate of sub-clinical LV dysfunction (LVEF , 50%) of Expert consensus for multimodality imaging evaluation of adult patients 26% at 6 months of follow-up after therapy. 233 As a result, this committee recommends follow-up at the completion of therapy for regimens including doses ,240 mg/m 2 . After exceeding the dose of 240 mg/m 2 , an evaluation before each additional cycle is considered prudent (Figures 13 and 15).…”
Section: Integrated Approachmentioning
confidence: 99%
“…In the study revealed a rate of sub-clinical LV dysfunction (LVEF , 50%) of Expert consensus for multimodality imaging evaluation of adult patients 26% at 6 months of follow-up after therapy. 233 As a result, this committee recommends follow-up at the completion of therapy for regimens including doses ,240 mg/m 2 . After exceeding the dose of 240 mg/m 2 , an evaluation before each additional cycle is considered prudent (Figures 13 and 15).…”
Section: Integrated Approachmentioning
confidence: 99%
“…Najpowszechniej akceptowanym patofizjologicznym mechanizmem kardiotoksyczności wywoływanej przez antracykliny jest hipoteza stresu oksydacyjnego, zgodnie z którą wytwarzanie wolnych rodników tlenowych i peroksydacja lipidów błony komórkowej powodują uszkodzenie kardiomiocytów. Uważa się, że rolę mogą odgrywać również inne mechanizmy [26][27][28][29][30][31]. Mechanizmy komórkowe i molekularne szczegółowo omówiono w dwóch pracach przeglądowych na ten temat [32,33].…”
Section: Antracyklinyunclassified
“…W przypadku schematów terapii obejmujących większe dawki antracyklin oraz u pacjentów z dużym początkowym ryzykiem proponuje się wcześniejszą ocenę czynności serca po podaniu łącznej dawki 240 mg/m 2 doksorubicyny (lub dawki równoważnej, patrz tab. 5) [10,31,85]. Początkowo można rozważyć oznaczenie co najmniej jednego biomarkera sercowego -troponiny (I lub T) oznaczanej metodą o dużej czułości lub peptydu natriuretycznego, a pomiar stężenia troponiny I metodą o dużej czułości proponuje się po każdym cyklu chemioterapii obejmującej antracykliny [86,87].…”
Section: Postępowanie Kardiologiczne U Pacjentów Stosujących Antracykunclassified
“…Increased aortic stiffness [3,4], endothelial dysfunction [5], and arterial remodeling [6] have been reported up to 1 year following Anth-C administration. However, in the present study and contrary to our hypothesis, Ea was not different at rest or during any stage of exercise.…”
Section: Vascular Structure and Function Are Not Different In The Yeamentioning
confidence: 99%
“…To date, investigators have focused almost exclusively on the cardiac-specific effects of Anth-C (primarily through evaluation of resting assessment of left ventricular ejection fraction [LVEF]), with minimal attention to vascular damage. Increased aortic stiffness [3,4], endothelial dysfunction [5], and arterial remodeling [6] have been demonstrated during or up to 1 year following Anth-C. However, whether these impairments in vascular structure (e.g., arterial stiffness and carotid intimamedia thickness [CIMT]) and function (e.g., endothelialdependent flow-mediated dilation [FMD]) persist in the years following Anth-C and whether they contribute to the impaired cardiac function observed in breast cancer survivors is currently unknown.…”
Section: Introductionmentioning
confidence: 99%